37=-2(22-X)+3(X-3)

Simple and best practice solution for 37=-2(22-X)+3(X-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 37=-2(22-X)+3(X-3) equation:


Simplifying
37 = -2(22 + -1X) + 3(X + -3)
37 = (22 * -2 + -1X * -2) + 3(X + -3)
37 = (-44 + 2X) + 3(X + -3)

Reorder the terms:
37 = -44 + 2X + 3(-3 + X)
37 = -44 + 2X + (-3 * 3 + X * 3)
37 = -44 + 2X + (-9 + 3X)

Reorder the terms:
37 = -44 + -9 + 2X + 3X

Combine like terms: -44 + -9 = -53
37 = -53 + 2X + 3X

Combine like terms: 2X + 3X = 5X
37 = -53 + 5X

Solving
37 = -53 + 5X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-5X' to each side of the equation.
37 + -5X = -53 + 5X + -5X

Combine like terms: 5X + -5X = 0
37 + -5X = -53 + 0
37 + -5X = -53

Add '-37' to each side of the equation.
37 + -37 + -5X = -53 + -37

Combine like terms: 37 + -37 = 0
0 + -5X = -53 + -37
-5X = -53 + -37

Combine like terms: -53 + -37 = -90
-5X = -90

Divide each side by '-5'.
X = 18

Simplifying
X = 18

See similar equations:

| (9-3x)(9-5x)= | | -11x^2+3x+11=0 | | 382=x+(x+6) | | (4/11)x=28 | | 3x-108=0 | | 7k-4k=12 | | x+.7=-.2 | | 3x=2(2x-3) | | k/2+5=8 | | s-32=-48 | | v+(v-30.8)+(v+27.3)=202.9 | | 3x^3-7x^2+6x-2=0 | | y^2+2x+8y+13=0 | | 12x^2-24-9=0 | | -7/9x23/4 | | x+(x+6)=382 | | x=-9/2-5/3 | | 4.2/-0.15 | | x-7.7=-3.5 | | -9/2-5/3 | | -11x^2+20x=0 | | 3x^3-7x^2=2-6x | | -27/12/-1/6 | | x-50=32 | | 25m^2-9/16 | | r+27=14 | | X-9=10/10(11-7x) | | x+30.8+x+27.3=202.9 | | -1/6(x-18)+1/2(x+2)=-4 | | 2/7x+4=16/7x | | 12(t-3)+3t=5(3t+4)-9 | | -5/7+2/3 |

Equations solver categories